Reply to the Letters to the Editor Concerning the Article: Alexandre Oliveira Ferreira, Andrea Riphaus. Propofol to Increase Colorectal Cancer Screening in Portugal. Acta Med Port 2014;27:541-42. - Riphaus, Andrea (2014)
Keywords: Colorectal Neoplasms; Hypnotics and Sedatives; Propofol; Endoscopy, Gastrointestinal; Colonoscopy.